Parallel Processing of Image Segmentation Data Using Hadoop - Akhtar, Nishat; Saleh, Junita Mohamad; Grelck, Clemens (International Journal of Integrated Engineering, 2018)
The use of sequential programming is slowly getting replaced by distributed and parallel computing which is widely being used in computing industries to handle tasks with big data and various high-end computing applications comprising of huge image and video data banks. Moreover, image processing using parallel computation is also gaining momentum in today’s technological era. Nowadays researchers are coming up with various methodologies to tackle high scale image processing applications by implementing parallel computing methodologies to carry out the specified image processing application task and simultaneously checking its performance against sequential programming. At the same time there are constraints on what can be done to maximize the task performance using high end multi-core CPU’s with advanced buses and interconnects that offer high bandwidth with low system latency. It is to be noted that there is no availability of standardized image processing task which can be used to evaluate a single node system. In this paper, we propose an efficient parallel processing algorithm to perform the task of image segmentation with the foremost aim to analyze the threshold of data size at which the proposed method outperforms sequential programming method in terms of task execution time by analyzing the distribution of average CPU cores usage and its threads over the execution time. The proposed methodology could be useful for researchers, as it can perform multiple image segmentation in parallel, which can save a lot of time of the user. For the purpose of comparison, we also implemented the same image segmentation task using sequential method of programming in an integrated development environment platform.